Super Vertex Magic Circulant Graphs
Let G = (V, E) be a finite simple graph with p = |V| vertices and q=edges, without any isolated vertex or any isolated edge. A vertex magic total labeling of the graph G is a bijection/from V U E to the set of consecutive integers (1,2, • ••